Barriers to Uptake of Postpartum Long‐Acting Reversible Contraception: Qualitative Study of the Perspectives of Ugandan Health Workers and Potential Clients. Issue 2 (8th April 2019) - Willcox, Merlin; King, Emma; Fall, Emma; Mubangizi, Vincent; Nkalubo, Julius; Natukunda, Silvia; Nahabwe, Haeven; Goodhart, Clare; Graffy, Jonathan
Abstract: Health workers have received training on delivering postpartum long‐acting reversible contraceptives (LARCs) through several projects in Uganda, yet uptake still remains poor. To understand the reasons, and to gather suggestions for improving uptake, we conducted individual semi‐structured interviews with a total of 80 postpartum parents, antenatal parents, health workers, and village health teams in rural south‐west Uganda. Interviews were recorded, transcribed, translated, and analyzed using qualitative thematic analysis. Specific barriers to uptake of immediate postpartum contraception for women included: the need to discuss this option with their husband, the belief that time is needed to recover before insertion of a LARC, and fear that the baby might not survive. Furthermore, social consequences of side‐effects are more serious in low‐income settings. Suggestions for improving uptake of postpartum contraception included health education by "expert users, " couples counseling during antenatal care, and improved management of side‐effects.